EIMERIOSIS IN GOATS FROM INDIVIDUAL FARMS IN POLTAVA CITY - Євстаф’єва, В. О.; Корчан, Л. М.; Корчан, М. І.; Мордовцева, О. М. (Scientific Progress & Innovations, 2014)
The data concerning the incidence, age and season eimeriosis dynamics in goats from individual farms in Poltava city. The species composition by causative agents of eimeriosis in goats represented by six species: Eimeria arloingi – 56 %; E. caprina – 30 %; E. alijevi – 28 %; E. ninakohlyakimovae – 15 %; E. jolchijevi – 12 %; E. christenseni – 6 %. Extensiveness of eimeriosis invasion in young stock of goats was 63–100 %, in goats older than one year, averaged, 85 %. In 56 % infected animals intensiveness of invasion averaged from a few hundreds to 10 thousands of oocysts in 1 g of feces. The most favorable to the eimeriosis was young stock of goats from 16 days to 4 months of age. The data of therapeutic efficacy antieimeriosis drugs for this invasion. The maximum efficiency on eimeriosis in goats showed by brovaseptol (effectiveness 100 %) and amprolinvet 12,5 % (ІЕ = 98,8 %, ЕЕ = 60,0 %).